Literatur Review: Faktor Resiko Sindrom Ovarium Polikistik pada Remaja: Literature Review: Risk Factors for Polycystic Ovary Syndrome in Adolescents - Wilda Qotrunnada Salsabila; Kartika Adyani; Friska Realita (Journal of Health, 2024)
Polycystic ovary syndrome (PCOS) is a complex metabolic, reproductive, and psychological disorder that impacts women throughout their lives. PCOS is a hormonal imbalance disorder that occurs in women of childbearing age. This can cause symptoms such as irregular menstruation, amenorrhea (absence of menstruation), anovulation (absence of ovulation), hirsutism, acne, and obesity. PCOS also causes metabolic disorders in the body. The exact cause of PCOS is not known but in general it can be caused by genetic and environmental factors. Many studies have proven the factors that influence PCOS. Therefore, to conclude the results of this research, a literature review was carried out. The literature was searched for scientific articles with the keywords "nutritional status", "physical activity", "mental health", "menstrual cycle", "PCOS" and "adolescence". Article search via Google Scholar and PubMed. After conducting a search, 9 articles were found that met the writing criteria. The results of the review show that several factors can significantly increase the risk of PCOS, namely, excessive nutritional status, lack of physical activity, poor mental health (stress and depression), and long and irregular menstrual cycles. The results of the review also prove that the main factors with the highest level of risk in this article are long and irregular menstrual cycles and excessive nutritional status